Comparison of Murotal Therapy and Classical Music Therapy on the Recurrence of Hallucinations in Patients - Mahdalena; Rahman, Aulia; Oktavia, Santi (Java Nursing Journal, 2025)
Background: Hallucinations are perceptual disturbances experienced by individuals, in which a person may hear, see, smell, or feel something that does not actually exist. This disorder carries the risk of causing behavior that is harmful to oneself and others. Purpose: This study aims to determine the difference in effectiveness between murotal therapy and classical music therapy on the recurrence of hallucinations in patients. Methods: This study used a pre-experimental design with a one-group pretest-posttest approach. A total of 30 patients diagnosed with hallucinations at the Aulia Rahma Clinic in Bandar Lampung were selected as respondents and divided into two intervention groups: the murotal therapy group and the classical music therapy group. Murotal therapy was conducted by playing Surah Ar-Rahman, while classical music therapy was provided through instrumental music. Findings: The results showed that the murotal therapy group experienced a 1.80-point decrease in hallucination recurrence scores, which was higher than the classical music therapy group. Data analysis using statistical tests showed a value of ρ = 0.032 (p < 0.05), which means that there was a significant difference between the two therapies in terms of reducing hallucination recurrence. Conclusion: Murotal therapy is more effective than classical music therapy in reducing the recurrence of hallucinations in patients with mental disorders. Murotal therapy can be used as an alternative non-pharmacological nursing intervention that is easy, inexpensive, and safe to apply in mental health nursing practice.